2010
DOI: 10.1007/s10867-010-9210-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback loops sustain repeating bursts in neuronal circuits

Abstract: Voluntary movements in animals are often episodic, with abrupt onset and termination. Elevated neuronal excitation is required to drive the neuronal circuits underlying such movements; however, the mechanisms that sustain this increased excitation are largely unknown. In the medicinal leech, an identified cascade of excitation has been traced from mechanosensory neurons to the swim oscillator circuit. Although this cascade explains the initiation of excitatory drive (and hence swim initiation), it cannot accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…It was previously reported that removal of the tail ganglion shortens swim duration in preparations with the head brain removed (Brodfuehrer et al 1993; Puhl and Mesce 2010; Friesen et al 2011). We were interested in determining whether the presence of the tail ganglion was necessary for the occurrence of the extended swims in preparations with only the SupraEG removed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously reported that removal of the tail ganglion shortens swim duration in preparations with the head brain removed (Brodfuehrer et al 1993; Puhl and Mesce 2010; Friesen et al 2011). We were interested in determining whether the presence of the tail ganglion was necessary for the occurrence of the extended swims in preparations with only the SupraEG removed.…”
Section: Resultsmentioning
confidence: 99%
“…Because cell 204 is a crucial component of the swim maintenance system (Weeks and Kristan 1978; Friesen et al 2011), cycle period can be considered a good measure of the excitation level in this system. We used this relationship to ask whether, in addition to extending swim duration, the maintenance system in SubEG-T preparations also has higher activity levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a further modeling effort synthesizing a career-spanning series of experimental studies, Friesen et al (2011) constructed a network model comprising multi-compartmental neurons of the entire swimming circuit, including trigger and gating neurons not shown in Fig. 2B.…”
Section: Swimming: a Cpg Modulated By Sensory Feedback And The Enviromentioning
confidence: 99%
“…On the other hand, neuronal activities of neurons have also been investigated by using PSpice tool or artificial neuronal circuit [41][42][43][44][45][46][47]. In the case for circuit implementation, the integrated circuits [51,52] are often used for building amplifiers or experimental circuit elements, while some researcher prefer to using commercial amplifiers as well because of its availabity and easy accessibility.…”
Section: Introductionmentioning
confidence: 99%